The Relevance of Behavior of Law Theory to Law Enforcement in Indonesia - Yazid Bustomi (Jurnal Hukum Prasada, 2022)
This article discusses the discrimination in legal treatment of the community that still occurs today. The principle of equality before the law cannot be fully implemented properly. The theory of behavior of law explains why this problem still occurs. The purpose of this study is to discuss what factors cause legal discrimination to occur. This legal research type is descriptive analysis. The type of data used is secondary data. The data collection method used is literature study, which is a technique to obtain secondary data through documents related to the problem, purpose and benefits of the research. This study uses qualitative data analysis techniques, namely data obtained from literature studies and then arranged systematically and then analyzed qualitatively to achieve clarity of problems to be discussed. The data is then analyzed interpretively using positive theory and law that has been outlined and then inductively drawn conclusions to answer the existing problems. The results of this study, that the factors of stratification, morphology, culture, organization and social control are the main factors in causing stratification. This factor causes people who have power to have easier access to the law than those who do not have power. This problem will continue continuously if law enforcement officers do not fix their morals. Massive, decisive and sustainable efforts are needed from all parties to change this legal culture.